2014
DOI: 10.1371/journal.pone.0104176
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorne Effect with Transient Behavioral and Biochemical Changes in a Randomized Controlled Sleep Extension Trial of Chronically Short-Sleeping Obese Adults: Implications for the Design and Interpretation of Clinical Studies

Abstract: ObjectiveTo evaluate the effects of study participation per se at the beginning of a sleep extension trial between screening, randomization, and the run-in visit.DesignSubjects were screened, returned for randomization (Comparison vs. Intervention) after 81 days (median), and attended run-in visit 121 days later.SettingOutpatient.PatientsObese (N = 125; M/F, 30/95; Blacks/Whites/Other, N = 73/44/8), mean weight 107.6±19.7 kg, <6.5 h sleep/night.InterventionNon-pharmacological sleep extension.MeasurementsSleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
(34 reference statements)
1
37
0
Order By: Relevance
“…53 Similarly, there is growing interest in developing interventions to treat insomnia as a means to improve metabolic regulation and reduce type 2 diabetes, 54 including an ongoing trial for sleep extension in an obese sample. 55 In light of this work, and the present results, additional treatment trials are warranted.…”
Section: 0 Discussionmentioning
confidence: 72%
“…53 Similarly, there is growing interest in developing interventions to treat insomnia as a means to improve metabolic regulation and reduce type 2 diabetes, 54 including an ongoing trial for sleep extension in an obese sample. 55 In light of this work, and the present results, additional treatment trials are warranted.…”
Section: 0 Discussionmentioning
confidence: 72%
“…The benefit of different “doses” of additional sleep has not been tested. However, put in perspective, certain pharmacological treatments deemed to be clinically efficacious to target sleep problems produce a ~15 minute increase in TST (Cizza, Piaggi, Rother, & Csako, 2014; Roth, Hull, Lankford, Rosenberg, & Scharf, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…As responses to our exit surveys indicated, one possible explanation for this finding is that these families were expecting to find out how their adolescents could get more sleep (even though we did not state this as the purpose). The impact of participants’ expectations entering a sleep extension study was illustrated in another recent trial in which adults with obesity experienced improvements in overall health even prior to randomization (Cizza, Piaggi, Rother, & Csako, 2014). One solution may be to not prime participants that the sole focus of the study is related to sleep or to do a full cross-over design in which all participants experience both experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on obesity (Cizza et al, 2014) showed that improvements in biochemical (fasting glucose, insulin, lipids) and behavioral (sleep duration/quality) parameters occurred between screening and randomization of the patients. These findings are consistent with the Hawthorne effect, which implies that behavior measured in the setting of an experimental study changes in response to the attention received from study investigators (Last, 1983).…”
Section: Perspectivementioning
confidence: 99%
“…As becomes clear from these findings, both the social propagation of expectations and the Hawthorne effect (Cizza et al, 2014) may influence the baseline of biochemical and behavioral parameters before patients are randomized to either placebo or active treatment, thereby potentially affecting the outcome of a study. In addition to the control and assessment of learning and expectation discussed earlier, future clinical trials should therefore also consider these elements.…”
Section: Perspectivementioning
confidence: 99%